History of Friedrich II of Prussia $1 (BVolume 10s - Carlyle, Thomas, 1795-1881 (Salt Lake City, UT : Project Gutenberg, 2008)
"History of Friedrich II of Prussia $1 (BVolume 10" by Thomas Carlyle is part of a six-volume biography published between 1858 and 1865. This monumental work chronicles the life of Frederick the Great of Prussia, born from Carlyle's decades-long fascination with the Prussian king. The project consumed thirteen years of intensive research, including battlefield visits across Germany and meticulous study of German histories. Carlyle's vivid portraits and masterful battle descriptions earned praise from literary giants and military students alike, cementing this as one of his greatest achievements. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/History_of_Friedrich_II._of_Prussia,_Called_Frederick_the_Great
Release date is 2008-06-16
Produced by D.R. Thompson and David Widger
Keywords: Social problems; Frederick II, King of Prussia, 1712-1786; Prussia (Germany) -- History -- Frederick II, 1740-1786